Text as Flags : The League of the South and the development of a nationalist intelligentsia in the United States 1975-2001 - Hague, Euan (Hagar: Studies in Society and Culture, 2002)
Th is paper examines the role of a group of intellectuals as the emergent leadership of a neo-Confederate nationalist organization called the League of the South (LS) that was formed in Tuscaloosa, Alabama in 1994. I argue that these intellectuals, primarily professional, accredited and recognized academics, comprise a nascent nationalist intelligentsia who developed a series of theories and historical interpretations that both connected with understandings about the past position of the Confederate States of America (CSA) and led them to propose its future revival. Tracing the academic production of and debate over these ideas, from their presentation in scholarly venues in the 1970s and 1980s to their role in supporting an outspokenly neo- Confederate nationalist politics in the 1990s, I claim that the nationalist sentiments of the individuals that produced them have shifted from ‘banal’ to ‘hot. ’ Over time, analyses forwarded by Grady McWhiney (b.1928), Michael Hill (b.1951) and Donald Livingston (b.1938) have solidified as a neo-Confederate nationalist ideology. In its promotion by the LS, within which these individuals have been leaders since its formation, this ideology currently underpins a wider neo-Confederate movement that is reaching out to established Confederate heritage groups such as the Sons of Confederate Veterans (SCV).